2016
DOI: 10.1093/annonc/mdw203
|View full text |Cite
|
Sign up to set email alerts
|

Pooled analyses of eribulin in metastatic breast cancer patients with at least one prior chemotherapy

Abstract: Eribulin is indicated in the EU for advanced/metastatic breast cancer patients following ≥1 prior chemotherapy for advanced disease, and anthracycline and taxane in adjuvant/metastatic setting. We pooled 1644 patients from two phase III trials and found that eribulin significantly increased survival versus control, particularly in some subgroups of interest like HER2- and triple-negative disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
75
2
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 10 publications
6
75
2
9
Order By: Relevance
“…The median OS, PFS, and TTF were 431, 325, and 155 in the overall cohort, and the ORR, CBR, and DCR were 34.6%, 44.2%, and 51.9%, respectively. In a pooled analysis of patients who had received at least one prior chemotherapy, the median OS and PFS for eribulin were 15.0 months and 3.9 months, respectively, while the CBR was 30% (15). Therefore, our results in this cohort of Japanese patients were generally similar to those in two European phase 3 trials (15).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The median OS, PFS, and TTF were 431, 325, and 155 in the overall cohort, and the ORR, CBR, and DCR were 34.6%, 44.2%, and 51.9%, respectively. In a pooled analysis of patients who had received at least one prior chemotherapy, the median OS and PFS for eribulin were 15.0 months and 3.9 months, respectively, while the CBR was 30% (15). Therefore, our results in this cohort of Japanese patients were generally similar to those in two European phase 3 trials (15).…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, several studies have demonstrated that eribulin is clinically-effective in patients with breast cancer (14,15). In a pooled analysis of patients with metastatic breast cancer who had received at least one prior chemotherapy regimen, eribulin significantly extended overall survival (OS), and increased the progression-free survival (PFS) and clinical benefit rates compared with the control treatments (15). The survival benefit of eribulin was also apparent in patients with human epidermal growth factor receptor 2 (HER2)-negative or triple-negative breast cancer (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ведущий научный сотрудник РОНЦ имени Н. Н. Бло-хина Л. Г. Жукова напомнила о результатах основных регистрационных исследований эрибулина в монотера-пии при диссеминированном РМЖ: EMBRACE, 301 ис-следование и их обобщенный анализ [8][9][10]. По дан-ным обобщенного анализа, наибольшее преимущество в плане увеличения общей выживаемости по сравнению с терапией по выбору врача и капецитабином получили пациенты с тройным негативным и HER2-отрицатель-ным РМЖ [10].…”
Section: ключевые слова: диссеминированный рак молочной железы эрибулинunclassified
“…Кроме того, совокупный анализ данных двух исследо-ваний (EMBRACE и 301) с учетом HER2 статуса и тройной негативной формы заболевания (был сделан по запросу Ев-ропейского агентства по контролю оборота лекарственных средств -EMA) продемонстрировал, что применение эри-булина сопровождалось улучшением ОВ в общей популяции по сравнению с контрольной группой [12]. Эта эффективность в отношении увеличения ОВ сохранялась в большинстве под-групп пациенток.…”
unclassified